Human Pluripotent Stem Cell-Derived Micropatterned Ectoderm Allows Cell Sorting of Meso-Endoderm Lineages - Yang, Yang; Laterza, Cecilia; Stuart, Hannah T.; Michielin, Federica; Gagliano, Onelia; Urciuolo, Anna; Elvassore, Nicola (Frontiers in Bioengineering and Biotechnology, 2022)
The human developmental processes during the early post-implantation stage instruct the specification and organization of the lineage progenitors into a body plan. These processes, which include patterning, cell sorting, and establishment of the three germ layers, have been classically studied in non-human model organisms and only recently, through micropatterning technology, in a human-specific context. Micropatterning technology has unveiled mechanisms during patterning and germ layer specification; however, cell sorting and their segregation in specific germ layer combinations have not been investigated yet in a human-specific in vitro system. Here, we developed an in vitro model of human ectodermal patterning, in which human pluripotent stem cells (hPSCs) self-organize to form a radially regionalized neural and non-central nervous system (CNS) ectoderm. We showed that by using micropatterning technology and by modulating BMP and WNT signals, we can regulate the appearance and spatial distribution of the different ectodermal populations. This pre-patterned ectoderm can be used to investigate the cell sorting behavior of hPSC-derived meso-endoderm cells, with an endoderm that segregates from the neural ectoderm. Thus, the combination of micro-technology with germ layer cross-mixing enables the study of cell sorting of different germ layers in a human context.